STUDIES ON INFLUENCE OF TROPICAL MARINE MACROALGAE EXTRACT Gracilaria verrucosa AS AN INHIBITOR FOR BIOCORROSION ON CARBON STEEL - FRANANTA S (NIM: 20514030), DIMAS
The primary metabolites of macroalgae commonly are used as food materials and its secondary metabolites are used as antimicrobes, antivirus, anticancer, apoptosis induction and other benefits. Tropical marine environment is highly corrosive to metals of construction material for marine transportation and pipelines to distribute oil and gas. Indonesia’s tropical marine macroalgaes have high potential and quality to be developed as an biocorrosion inhibitor for metals in tropical marine environment. Therefore this study was conducted to determine the bioactivity from Indonesia’s tropical marine macroalgae extract Gracilaria verrucosa which derived from Sayang Heulang Beach, Pameungpeuk, District of Garut,West Java to inhibit biocorrosion on carbon steel. This study was begun from extraction of tropical marine macroalgae Gracilaria verrucosa. Crude extract of Gracilaria verrucosa was obtained from extraction result by Folch method (chloroform:methanol:phosphate buffer, 2:1:0.8 (v/v)). Crude extract of methanol-aqueous and chloroform phase was produced respectively 33.38% and 0.93% (w/w). Crude extract which has the biggest activity to inhibit biocorrosion was methanol-aqueous phase through visualization qualitative test using commercial nail in solid media of bacteria Thiobacillus ferrooxidans during 3 days of incubation time with room temperature and dark condition. Then crude extract of methanol-aqueous phase was further separated by using column chromatography with silica G-60 7733 and a stepwise elution hexane:acetone (8:2, 5:5, 2:8 (v/v)) and methanol p.a. The separation produced 6 fractions which have been analyzed by UV Spectroscopy in wavelength scale 190 – 380 nm. Quantitative test of ability to inhibit biocorrosion with weight loss method of carbon steel coupon in liquid media of bacteria as a test-media by adding 0.5% (v/v) from six fractions and shaked in room temperature with the velocity 150 rpm during 96 hours and dark condition. The result of quantitative test showed that there were 2 active fraction namely fraction B and F which respectively have the lowest corrosion rate (24.60 ± 1.70 mpy and 20.93 ± 0.18 mpy) and the highest of inhibition efficiency (46.57% and 54.53%). Continued analysis for determination of corrosion rate in concentration variation to observe optimum concentration from each active fractions. This result of quantitative test showed that the lowest corrosion rate was obtained in addition of 1.5% (v/v) concentration from fraction B with corrosion rate as much as 33.82 ± 1.89 mpy and fraction F in concentration 0.5% (v/v) with corrosion rate as much as 38.41 ± 2.76 mpy. By means of optimum concentration which obtained from each fraction then analysis was continued by quantitative test with time variation during immersed periode of 432 hours. The test result showed that there was an increasing of weight difference from carbon steel which be linier against periode of immersion. Analysis of morphology structural and chemical composition on the surface of carbon steel coupon which have been exposed in liquid media of bacteria during immersed time 96 hours with and without fraction F inhibitor in optimum concentration as much 0.5% (v/v) was conducted by using SEM-EDS instrument (Scanning Electron Microscopy-Energy Dispersive Spectroscopy). The result of SEM morphology analysis on the surface of carbon steel coupon without any inhibitor showed that there were much irregular multipore hole with high quantity of bacteria cells Thiobacillus ferrooxidans if it was compared with the surface of carbon steel coupon with fraction F inhibitor. Fraction F inhibitor has an ability to form a flaky cracked layer to inhibit the activity of bacteria Thiobacillus ferrooxidans to oxidize iron faster and all at once to inhibit the growth of bacteria. The result of chemical composition analysis on the surface of carbon steel coupon could be used to study the biocorrosion mechanism and also to show that the precipitation that formed as an part of biofilm layer was precipitation of iron (III) hydroxide and iron sulfide. Identification of UV spectrum for both fraction showed that fraction B and F were mixture of phenolic and flavonoid compounds.